2015
DOI: 10.1111/apt.13156
|View full text |Cite
|
Sign up to set email alerts
|

Low muscle mass and sarcopenia: common and predictive of osteopenia in inflammatory bowel disease

Abstract: Low lean mass and sarcopenia are common in patients with IBD, and important to recognise as they predict osteopenia/osteoporosis. Grip strength testing should be incorporated into routine clinical practice to detect low lean mass deficits, which may go unrecognised using BMI alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 62 publications
10
105
0
5
Order By: Relevance
“…13,14 In addition to malnutrition, changes in body composition such as the occurrence of sarcopenia have been described in patients with CD. [15][16][17][18] Schneider et al describe the occurrence of sarcopenia in 60% of patients with CD even during clinical remission. 18 Loss of lean mass (LM) has been associated with worsening of bone mineral density, increased morbidity, loss of muscle strength, and increased risk of infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In addition to malnutrition, changes in body composition such as the occurrence of sarcopenia have been described in patients with CD. [15][16][17][18] Schneider et al describe the occurrence of sarcopenia in 60% of patients with CD even during clinical remission. 18 Loss of lean mass (LM) has been associated with worsening of bone mineral density, increased morbidity, loss of muscle strength, and increased risk of infectious complications.…”
Section: Introductionmentioning
confidence: 99%
“…These relationships support this criticism of using albumin as a marker of nutritional status, as any relationship between serum albumin and nutritional status may simply be a reflection of more severe inflammatory illness, rather than an indicator of nutritional compromise. Interestingly, Bryant et al 14 found low serum albumin (,34 g/dL) in only 7% of their cohort with UC, whereas 26% were found to have reduced functional lean mass according to the ASM index. Sixty-four percent of their patients had active disease.…”
Section: Are Patients With Uc Nutritionally Compromised? Nutritional mentioning
confidence: 92%
“…These changes, suggestive of malnutrition, were not related to disease location, duration, or activity. More recently, utilizing dual-energy X-ray absorptiometry, Bryant et al 14 described appendicular skeletal muscle (ASM) mass, as a reflection of true muscles mass in adult patients with UC. Of their cohort of 42 patients, 26% demonstrated an ASM index ,1 standard deviation and were considered to have low lean mass; however, fat mass was not considered reduced.…”
Section: Are Patients With Uc Nutritionally Compromised? Nutritional mentioning
confidence: 99%
“…However, Bryant et al [8] noted an odds ratio of 2.03 for sarcopaenia in older patients who had received more than 12 months of steroid treatment, and Jahnsen et al [29] saw a decrease of lean tissue mass that was concentrated in patients who had received steroids. [60] 106 cases of CD (adults, > 1 yr duration), 75 age- & sex-matched previously healthy acute hospital admissions with illness of < 28 days duration…”
Section: Reviewmentioning
confidence: 99%